A New Index Number and its Meaning - Haberler, Gottfried (Quarterly Journal of Economics, 1928)
I. Mr. Snyder's broad Index number, 434.—II. There is no one concept of price level that serves all purposes, 435.—III. The index appropriate for the measurements of real income, 436.—IV. That for deferred payments, 441.—V. Should the price index take account of producers' goods? 443.—VI. The price index with reference to business cycles, 445.—VII. The Snyder index as means of computing the rapidity of circulation of money, 447.